Bulharsko a Bulhaři očima českého turisty: O trnitých stezkách mezietnického dialogu - Penčev, Vladimir (Lidé města, 2003)
The process of the Czech Republic's integration into the European Union is evidently bringing some unexpted prospects. Most recently one could obviously see a certain political will to close the state border in the East and to curtail the access of Europeans from the Balkans to the Czech Republic. The author thinks of the question of how the new social situation influences the approach to Bulgarians and Bulgaria among that part of Czech society which visits Bulgarian seaside resorts. Moreover, it inspects the question of whether the approach is determined from the position of ethnic feeling or civic identity. He formulates the conclusions on the basis of his own field survey he carried out through the questonnaire method (including direct interviews and observation) in the summer of 1997 and 1998 in two Bulgarian seaside resorts - Sozopol and Primorsko. He addressed 120 respondents. The questions basically focused on the Czech tourists´ general knowledge of Bulgaria prior to the visit to Bulgaria, their ideas about Bulgarians at the association level and in this context the typical features or Bulgarians and everything Bulgarian depicted by them. The research also focused on the frequency and quality of contacts with the Bulgarian environment and finally on the question of whether there are ethno-stereotypes of Bulgarians in the Czech environment and what are the parametres of the ethno-stereotypes. The author has found that there is certain knowledge of Bulgaria´s geography. On the other hand, there is selective knowledge of Bulgarian culture and day-to-day life (seen through the prism of cuisine and food and seaside resorts), which contrast with relatively rich knowledge of the personalities of Bulgarian culture and political scene. There are large discrepancies in the knowledge of Bulgaria's ethnic composition. ln the Czechs´ consciousness mainly Romanies and Turks come to the foreground. The research has revealed a positive approach of Czech tourists to Bulgaria, but not any consciousness of kinship of the two natioos. In the consciousness of the tourists under consideration one can find a model of Bulgarian distinctiveness which serves as a basis for a search for paradigms of some common element . The joint Slav origin and the mission of St Cyril and Methodius are almost exclusively denoted as linking elements.